ANALISIS KINERJA KONTROL ELEKTRIK PADA MOTOR LISTRIK BLDC : PERFORMANCE ANALYSIS OF ELECTRICAL CONTROLS IN BLDC ELECTRIC MOTORS - Sayful Rozzy (Program Studi Teknik Mesin PSDKU Polinema Kediri, 2024)
Hybrid Motor is one of the newest technologies being developed to reduce dependence on the use of fossil fuels by utilizing electrical energy as a source of propulsion. The working principle of this motor is to convert electrical energy into mechanical energy so that the vehicle can run. In the preparation of a Hybrid Motor there is one component called a BLDC (Brushless Direct Current) Motor, a BLDC motor is one of the main components in a Hyrid Motor which functions as a propulsion device. In moving the speed of the motor, of course, a device called a controller is needed. This controller utilizes a source of electrical energy from the battery to be able to operate and control the performance of the BLDC motor. The BLDC motor controller plays an important role in controlling the supply of electrical energy flowing to the motor to produce the desired rotation and torque. This supply of electrical energy is needed to operate the components in the BLDC motor controller so that it can control the performance of the BLDC motor. This research aims to analyze the effect of varying vehicle loads and speeds on the value of the supply voltage and electric current required by the controller. The research results show that an increase in vehicle load and speed causes a decrease in the value of the controller input voltage. As the load and speed increase, the voltage value at the controller input decreases as more energy is applied to the motor coils to produce the required torque. Then the value of the controller input current has increased because to produce torque that is in accordance with the amount of load and increased vehicle speed, the current flowing to the motor needs to be increased. This shows that there is a relationship between the increase in load and vehicle speed on the value of the input voltage and current of the controller